Development of microwave antenna for cancer treatment - Nurfarhana, Mustafa; Nur Hazimah Syazana, Abdul Razak; Nurhafizah, Abu Talip Yusof; Mohamad Shaiful, Abdul Karim (Springer, Cham, 2021)
For cancer treatment,microwave thermotherapy method is widely used especially for liver cancer treatment by using a coaxial biomedical applicator device. This device is used to transfer heat from microwave generator to liver tissue in order to kill cancerous tissue. Neglecting the impedance matching between the applicator and the liver tissue can lead power reflection to the power supply or loss into the surrounding healthy tissue. The impedance of the applicator is hugely dependent on the structure and dielectric material used as the insulator for the biomedical applicator. In this work, we aim to study the best structure of the applicator, which can minimize the impedance mismatch. There are two phases required in order to achieve the aim. In first phase, parameter of the applicator has been estimated using the characteristic of impedance for coaxial structure. In phase two, the biomedical coaxial applicator is designed using the electromagnetic simulator software and the results were analyzed to identify the best parameter used for the design. The result of return loss obtained at 2.45 GHz is −25.42 dB with impedance of 21.23. From the value of return loss, 0.29% of power will be reflected to the generator or surrounding tissue while another 99.71% of power will be transmitted into the cancer cell. Based on the finding, most power is transmitted efficiently to the liver and less power is reflected to the surrounding which means it is harmless to the surrounding tissue.